Collaborative Regional Management in Addressing Complex Local Governance Challenges: JEL Classification: D73; H11; H70; H83; R58 - Muhammad Arsyad; Risma Niswaty; Nuralamsyah Ismail; Suciati Suciati (Generasi Sains Indonesia, 2026)
This study examines the role of collaborative regional management in addressing complex local governance challenges. The research aims to analyze the influence of stakeholder participation, institutional coordination, collaborative leadership, and accountability mechanisms on governance effectiveness within regional governance systems. A quantitative approach was employed using a cross-sectional survey of 228 respondents involved in regional governance activities. Data were analyzed using Structural Equation Modeling with the Partial Least Squares approach. The findings reveal that all dimensions of collaborative regional management significantly contribute to governance effectiveness, with collaborative leadership emerging as the strongest predictor, followed by institutional coordination, stakeholder participation, and accountability mechanisms. The study introduces a multidimensional collaborative regional management framework that integrates key governance dimensions into a comprehensive model for addressing governance complexity. This framework represents the primary novelty of the research. The findings provide theoretical insights into collaborative governance literature while offering practical guidance for policymakers seeking to strengthen governance capacity, institutional resilience, and policy effectiveness in increasingly complex governance environments.